(untitled) (Intent Research Scientific Journal, 2023)
Great thinker, poet, founder of the Turkish language Mir Alisher Navoi was born in 1441 in Hirat. He was famous poet and wrote many gazels, poems and rubois. The world recognized him with “Hamsa”. “Hamsa” included 5 epics and all people read it still. Navois works have been translated into many languages. Translations of Navoi’s works can be read in many languages of the world. The first translations were made in 1557 into the Italian language by Christopher Armeno.[2] Later, the poet’s works were translated by many translators of the world. But large-scale events to celebrate the 500th anniversary of the poet took place in 1938. This year, a commission was established under the Council of Ministers of Uzbekistan to hold celebrations on the occasion of the anniversary of the great classic. According to the commission’s plans, the events were to be held in Tashkent and Moscow. On March 12, 1941, a government decree appeared on holding two anniversary celebrations - the 500th anniversary of Alisher Navoi and the 800th anniversary of Nizamiy Ganjavi.